Teaching Learning Activities Among Students with Physical Disabilities - Shiwakoti, Rabindra; Dahal, Hira; Shiwakoti, Krishna Prasad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2024)
The main aims of this study is to analyze the current scenario of teaching learning practices among students with physically disabilities in their study area. This study analyzes existing instructional practices used for students with physical disabilities, find out challenges in teaching students, and suggest appropriate instructional techniques for academic output of the students. The study was conducted through general qualitative research design with interpretive paradigm. The respondents of this study are physically disabled students, head teacher of the school who is physically disabled and teachers teaching students with physically disabled. Two schools from Kathmandu district is selected purposively. In-depth interview, observation, and focus group discussion were used in this study to collect primary data. Two student-respondents from the school were interviewed from the secondary level. Six teachers and one head teacher from selected schools were also interviewed. So, our total respondents in this research are 18. The collected data is analyzed using thematic analysis, a systematic approach involving several key steps. The themes are reviewed and refined through discussion and comparison with the original data. Creating inclusive learning environments, providing assistive technology, modifying curriculum and assessments, and promoting self-advocacy and independence are the major steps which can be implied in teaching/ learning process for better output of disabled students. The study also suggests for the appropriate instructional techniques to be used for academic improvement of the students with physical disabilities. By embracing a student-centered approach and fostering a supportive and inclusive learning community, educators can empower students with physical disabilities to reach their full potential physically, mentally, academically and socially well.